2022
DOI: 10.1002/env.2781
|View full text |Cite
|
Sign up to set email alerts
|

A vector of point processes for modeling interactions between and within species using capture‐recapture data

Abstract: Capture-recapture data and corresponding models have been used extensively to estimate the size of wildlife populations when detection probability is less than 1. When the locations of traps or cameras used to capture or detect individuals are known, spatially-explicit capture-recapture models are used to infer the spatial pattern of the individual locations and population density. Individual locations, referred to as activity centres, are defined as the locations around which the individuals move. These activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In many cases, the distribution [s] serves as a prior and is specified as a bivariate uniform distribution over the study area, which implies a complete spatial random point process for s i before the data are observed. Various approaches have been proposed to generalize the model for s i such as allowing it to be a heterogeneous spatial point process (e.g., Diana et al, 2022;Sutherland et al, 2015). Following the procedure we described in the previous section, we express the posterior distribution associated with the SCR model as…”
Section: Multistage Computing For Spatial Crmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, the distribution [s] serves as a prior and is specified as a bivariate uniform distribution over the study area, which implies a complete spatial random point process for s i before the data are observed. Various approaches have been proposed to generalize the model for s i such as allowing it to be a heterogeneous spatial point process (e.g., Diana et al, 2022;Sutherland et al, 2015). Following the procedure we described in the previous section, we express the posterior distribution associated with the SCR model as…”
Section: Multistage Computing For Spatial Crmentioning
confidence: 99%
“…In many cases, the distribution false[boldsfalse]$$ \left[\mathbf{s}\right] $$ serves as a prior and is specified as a bivariate uniform distribution over the study area, which implies a complete spatial random point process for boldsi$$ {\mathbf{s}}_i $$ before the data are observed. Various approaches have been proposed to generalize the model for boldsi$$ {\mathbf{s}}_i $$ such as allowing it to be a heterogeneous spatial point process (e.g., Diana et al, 2022; Sutherland et al, 2015).…”
Section: Multistage Computing For Spatial Crmentioning
confidence: 99%
“…Time‐varying individual covariates present challenges in the study of marked animals in wild populations. Whether researchers are interested in the effects of breeding status (Pradel, 2005), location (Borchers & Efford, 2008; Diana et al, 2022; McLaughlin & Bar, 2021), or measures of fitness like body mass (Bonner & Schwarz, 2006) or parasite load (Argáez et al, 2020), these variables can only be observed when an animal is detected by physical capture or other means. The resulting data will have many missing values that need to be handled in some way.…”
Section: Introductionmentioning
confidence: 99%